2019
DOI: 10.15627/jd.2019.6
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Sky View Factor on Air temperature in High-rise Urban Residential Environments

Abstract: Urban geometry is defined by the height, length, width, and distance of buildings, which affect the urban environment and its microclimate, especially a high-rise and high-density urban environment, such as Tehran. In this regard, the Sky View Factor (SVF) may often be a desirable criterion in identifying the interaction between urban geometry and the air temperature in densely populated areas. The research aim was to investigate the SVF in an urban microclimate of a high-rise residential complex and to evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Contrarily, in high-rise urban residential environments in Tehran, Iran [14], it was found that during the hottest and the coldest days in the year, there was a direct relation between SVF and air temperature during the day and an inverse relation at night. In the temperate oceanic climatic region, such as southern Brazil, which has dry winter seasons [10], it was found that the variation in T mrt was closely related to the variation in SVF.…”
Section: Introductionmentioning
confidence: 99%
“…Contrarily, in high-rise urban residential environments in Tehran, Iran [14], it was found that during the hottest and the coldest days in the year, there was a direct relation between SVF and air temperature during the day and an inverse relation at night. In the temperate oceanic climatic region, such as southern Brazil, which has dry winter seasons [10], it was found that the variation in T mrt was closely related to the variation in SVF.…”
Section: Introductionmentioning
confidence: 99%
“…The microclimate at the street level is inf luenced by urban geometry, which includes factors such as aspect ratio, sky view factor, and street orientation (Ahmadi Venhari et al, 2019;Jamei & Rajagopalan, 2015;Krüger, 2011). The street orientation and aspect ratio of buildings determine solar exposure and shadow patterns, affecting surface and air temperature variations throughout the day (Baghaeipoor & Nasrollahi, 2019;Cliff Moughtin, 2003;Svensson, 2004). In additional, the density of buildings can inf luence wind speed, leading to changes in thermal conditions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This factor is influenced by the components of the urban fabric, street furniture and trees: values close to 1 correspond to a large visible portion, while values close to 0 indicate a limited view of the sky. SVF can be classified into four categories [73,74]: SVF < 0.25, dense space; 0.25 < SVF < 0.50, semi-dense space; 0.50 < SVF < 0.75, semiopen space; and SVF > 0.75, open space. Moreover, SVF plays an important role in the description of urban radiation properties: the higher its value, the greater the incidence of direct solar radiation (Jiao et al, 2019).…”
Section: Sky View Factor (Svf)mentioning
confidence: 99%
“…Concerning urban morphology, mean SVF equal to 0.80 suggested the predominance of open spaces [73,74], resulting in a high sky exposure and a greater amount of solar radiation (RJ = 5236.5 Wh/m 2 , on average) with respect to the cool-spots (SVF = 0.69 and RJ = 4505.19 Wh/m 2 , on average).…”
Section: Hot-spot Sitesmentioning
confidence: 99%